(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
Research and development in science and innovation have changed consumer awareness of conventional food sources to functional foods that provide more nutrition and health. On the other hand, there is an emerging no for cow milk due to environmental and ethical considerations. Plant-based milk alternatives emerged as a rising trend, serving as an inexpensive alternative to a poor economic group of developing countries and in places where cow’s milk supply is insufficient. A functional food should promote cognitive response, an improved immune system, and general well-being. Though there are several plant-based milk substitutes, using vegetables to produce a novel milk substitute still needs to be considered. Hence, this review aims to incorporate potatoes to produce a milk-like substitute due to their high nutritious content, bioavailability, and environmental sustainability. Potatoes are a better source of protein, vitamins, and minerals than rice, wheat, sorghum, legumes, and corn, with a high number of antioxidants and phytochemicals. With consumers becoming increasingly aware of the association of diet, nutrition, and health, potatoes have the potential to become an important dietary source of bioactive ingredients, i.e., functional food.